A transdiagnostic psychosocial prevention-intervention service for young people in the Republic of Georgia: early results of the effectiveness study. Issue 1 (31st December 2022) - Makhashvili, Nino; Javakhishvili, Jana Darejan; Chikovani, Ivdity; Bevan-Jones, Rhys; Uchaneishvili, Maia; Pilauri, Ketevan; Shengelia, Natia; Marjanishvili, Nutsa; Sulaberidze, Lela; Sikharulidze, Keta; Roberts, Bayard; Bisson, Jonathan
ABSTRACT: Background: The decade between the ages of 14 and 25 is a particularly vulnerable period for the development of mental health problems, especially of common mental disorders. Mental health and psychosocial prevention and support services for young people in the Republic of Georgia have been extremely limited, leaving a wide treatment and care gap. Club Synergy was designed as an innovative, pragmatic solution that is responsive to the needs of young people and incorporates all necessary levels of care required (prevention, early identification & intervention, and treatment) into a single, trauma-informed service that uses a transdiagnostic approach. This paper presents preliminary findings from the pilot phase of establishing and running the service. Aim: To examine the characteristics of young people presenting to Club Synergy and the effectiveness of contact with the service. Methods: Quantitative evaluation of a consecutive series of young people seen by Club Synergy between November 2019 and July 2020. Demographic information was analysed using descriptive statistics. Pre–post outcomes for anxiety (GAD-7), depression (PHQ-9) and health-related quality of life (EQ-5D-5L) were analysed using the Wilcoxon signed-rank test. Results: Hundred and seventy-four young people were included. The majority (68.9%) self-referred, with referral from The Ministry of Justice due to conflict with law (23%) accounting for most of the other young people seen. Emotional disturbance (73.6%), anxiety (60.3%), problems in interpersonal relationships (57.5%) and low mood (49.4%) were the commonest presenting symptoms. Seventy-three per cent reported 4 or more adverse childhood experiences. After engaging in transdiagnostic modules, median baseline scores for depression and anxiety reduced by 40% and 45%, respectively, and self-rated health improved by 14%. Conclusions: Preliminary analysis indicates that Club Synergy's trauma-informed model of care, based on a transdiagnostic approach, has the potential to provide an effective service to young people in Georgia at risk of developing and with mental health problems. HIGHLIGHTS: This pragmatic study of a newly established mental health service for young people in Georgia suggests that a trauma-informed approach, using transdiagnostic modules, has the potential to effectively prevent and treat common mental health presentations.